Functional and stylistic features of neologisms in the Ukrainian-language segment of the social network "Twitter" - Kozka, Davyd (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article outlines and analyzes the functional and stylistic parameters of neologisms in the Ukrainian-language segment of the social network "Twitter". The research data is based on more than two thousand Ukrainian-language Twitter posts in 2020-2024. Given the specifics of network, whose main purposes of which are providing communication and information, the following functions of neologisms in tweets are distinguished: nominative, communicative, attention- grabbing, influence-related, and pragmatic. The nominative function of the named words in tweets realizes the need to give new realities, individuals, phenomena, and events names that do not yet exist either in general usage or in lexicographical works. Neologisms also serve as a means of self-nomination and are part of aphorisms and paraphrases. The structure of tweets that represent the attention-grabbing function includes marker lexemes, with the help of which the author encourages online communicators to pay attention to a certain event, phenomenon, situation, or give their own assessment of it. Neologisms are used in interrogative statements, prompting communicators to hold their attention on posts, reflect on the information presented in them, and sometimes take the position of the tweet author in a reply. The cognitive function of neologisms is to verbalize the ability of the author of a tweet to understand, perceive, and learn information, i.e. to activate the author’s speech and nominative activity with his or her pragmatic instructions. The analysis of the factual material suggests that since tweets are representatives of the author’s views, and value judgments regarding certain events, concepts, and phenomena, it is advisable to distinguish the pragmatic function of neologisms in tweet expressions. The use of neologisms in tweets is influenced by pragmatic factors that reflect the author’s attitude to the message; pragmatic information in tweets is expressed in evaluative neolexemes derived in different ways and represented mainly by noun and adjectival formations. The article focuses on analyzes neologisms with the morpheme ze-, which has recently become a productive class of neologisms.